Study on Frequency of Irritable Bowel Syndrome Among The Students of Rajshahi Medical College (Bangladesh Journal of Medicine, 2015)
Background: This study was carried out to find out the frequency of IBS, symptoms pattern, health care seeking behavior among the students of Rajshahi Medical College.Objectives: To find out the frequency of IBS among the students of Rajshahi Medical College, determine the pattern and frequency of gastrointestinal symptoms in students with IBS and find out health care seeking behavior of IBS subjects.Methods: An observational descriptive cross sectional study was carried out after collecting data from 320 students of Rajshahi Medical college who fulfill inclusion and exclusion criteria by inviting them to filled out a questionnaire based on Rome III criteria for diagnosis of IBS from July 2009 to June 2010Results: A total of 320 students with male 50%(160/320) and female50%(160/320)were included in this study. The overall frequency of IBS among the students of Rajshahi Medical college was32.5% with 35% in man and 30% in women. Abdominal pain or discomfort was present in 100% students with altered frequency of stool in 78.84%(P=0.00), altered stool consistency 80.00%(p=0.00) and pain relieved by defecation was present in 67.30%(p=0.00).Overall consultation rate in students of Rajshahi Medical College were 46.2% with 70.2% in male and29.8% in female (p=.001).Conclusion: There was a higher frequency of irritable bowel syndrome among the students of Rajshahi medical college than the general population of Bangladesh. About half of them indeed seek health care advice. However the results of this study need to be confirmed in a large multi centre study.Bangladesh J Medicine Jan 2015; 26 (1) : 5-8